Praktik Dokter Dalam Pemberian Pelayanan Kesehatan Pada Pasien HIV dan AIDS di Rumah Sakit Rujukan di Kota Semarang - Miralda Septri Dewi; Zahroh Shaluhiyah; Antono Suryoputro (Jurnal Promosi Kesehatan Indonesia, 2017)
Background: Semarang City had a highest cases of HIV and AIDS in Central Java. In order to provide health care service for People with HIV and AIDS (PLWHA), three from the five designated hospitals were actively providing Care, Support and Treatment (CST) as a referral hospital for PLWHA in Semarang City. HIV-related discrimination is one of the barrier in the response to HIV and AIDS that influenced PLWHA to seek HIV treatment and lost of HIV treatment because they were afraid of getting stigma and discrimination in health care facilities. Some research have indicated that there were stigma and discrimination by health workers, including doctors. This study aims to find out doctors practices in providing health care to patients with HIV and AIDS in a referral hospital in Semarang City.Method: This study used qualitative methods. The data collecting used indepth interview. The data was collected from 13 doctors as a primary informants and triangulation with 3 HIV team leader.Results: The results showed that the majority of doctors practice was good, they did not discriminate when providing care or treatment to patients with HIV and AIDS. However, there were still a some doctors who discriminate when providing care for patients with HIV and AIDS such as the use of Personal Protective Equipment (PPE) was more strictly when dealing with patients of PLWHA like using double gloves. Most doctors have a good knowledge and positive attitudes towards HIV and AIDS. However, there were some doctors who has less understanding of HIV and AIDS.Keywords : doctor practice, HIV and AIDS patients, hospitals